THE PART OF SUPERVISION IN MAKING EDUCATION BETTER - Asy’Ari, Ach. Baidlowi; Mardiyah; Thohir, Muhammad (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The main problem in this study is the poor quality of education, which comes from the weak way educational supervision is carried out in schools. Supervision is very important because it helps, guides, and improves teachers' skills, making the learning process work well and smoothly. The goal of this study is to look at how supervision can help improve education quality by making teachers perform better and making learning more effective. This study uses a qualitative method with a descriptive approach. Information was gathered through detailed interviews, observations, and reviewing documents with school principals, teachers, and supervisors. The data was analyzed in three steps: reducing the data, presenting it, and drawing clear conclusions. The findings show that when supervision is planned, ongoing, and done together, it helps teachers get better at planning lessons, managing classes, and sharing results about student learning. The discussion shows that the success of supervision depends a lot on the supervisor's skills, good communication, and support from the school's environment. In conclusion, supervision is more than just watching over; it's also about helping teachers grow and improve. When supervision is done in a caring, involved way that focuses on what teachers need, it really helps make the school environment better and supports higher quality teaching.